Numerical modeling of detonation and action of gas-cumulative charges on solid obstacles - Abouziarov, Mustafa Khasianovich; Kochetkov, Anatoliy Vasilievich; Krylov, Sergey Valerievich; Tsvetkova, Yelena Valerievna (Computational Continuum Mechanics, 2008)
A numerical method for solving plane and axisymmetric coupled problems of detonation of gas-cumulative charges and their action on elastoplastic obstacles is presented. The method, which is based on a modified Godunov scheme, is used to calculate the energy release during detonation and gas motion as well as the dynamic deformation of elastoplastic obstacles. The results of the numerical analysis of high velocity gas jet generation in plane short П-charges are described. The influence of the charge shape on the gas-cumulative jet parameters is examined. The results of investigation of the interaction between the cumulative jets and the steel plate mounted on a ground base are given. The results of numerical simulations are in qualitative agreement with the available experimental data.